Ventricular Fibrillation Triggered by PVCs from Papillary Muscles: Clinical Features and Ablation. (23rd July 2014) - SANTORO, FRANCESCO; BIASE, LUIGI DI; HRANITZKY, PATRICK; SANCHEZ, JAVIER E.; SANTANGELI, PASQUALE; PERINI, ALESSANDRO PAOLETTI; BURKHARDT, JOHN DAVID; NATALE, ANDREA
VF from Papillary Muscle Background Animal studies showed that papillary muscles can be sources of ventricular fibrillation (VF) in both the left and right ventricle, but this occurrence in humans has been described only in patients with ischemic heart disease. Objective To investigate the role of papillary muscle premature ventricular contractions (PVCs) as triggers for VF and the safety and feasibility of catheter ablation in these patients. Methods Six patients (2 male; age, 40 ± 11 years; 5 with a normal structural heart and 1 with nonischemic cardiomyopathy) with history of VF resulting in repetitive implantable cardioverter defibrillator shocks, despite antiarrhythmic drug therapy, and a papillary muscle focus of PVCs triggering VF were included and underwent mapping and ablation of PVCs. Results PVCs were observed to trigger VF and localized by mapping the earliest activation point that matched pace mapping of the same area. In 2 patients, PVCs originated from the left ventricle at the posteromedial papillary muscle; in 4 patients, PVCs originated from the right ventricle, at the posterolateral papillary muscle. Elimination of the triggering PVC was obtained in these areas after 19 ± 12 minutes by radiofrequency application. During a follow‐up of 58 ± 11 months using ambulatory monitoring and defibrillator memory interrogation, no patients had recurrence of symptomatic ventricular arrhythmias. Conclusion Papillary muscles from both ventricles represent an anatomic structure potentially involved in the onset of VF, also in normal structural heart. PVCs arising from this area can be successfully eliminated by radiofrequency ablation, resulting in freedom from recurrent VF at long‐term follow‐up.